(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
Finite element analysis is an effective method of determining the static performance of structuresfor three reasons which are saving in design time, cost effective in construction and increase the safety of the structure. Previously, it is necessary to used advanced mathematical methods in analysis large structures, such as bridges, tall buildings and other. More accuracy generally required more elaborate techniques and therefore a large friction of the designer’s time could be devoted to mathematical analysis. Finite element methods free designer’s from the need to concentrate on mathematical calculation and allow them to spend more time on accurate representation of the intended structure and review of the calculated performance. Furthermore, by using the programs with interactive graphical facilities, it is possible to generate finite element models of complex structures with considerable ease and to obtain the results in a convenient, readily assimilated form. This may save valuable design time. More accurate analysis of structure is possible by the finite element method leading to economics in materials and construction also in enhancing the overall safety